Novel tumor necrosis factor-related long non-coding RNAs signature for risk stratification and prognosis in glioblastoma - Long, Shengrong; Wu, Bingbing; Yang, Liu; Wang, Lesheng; Wang, Bo; Yan, Yu; Jiang, Jiazhi; Yang, Bin; Zhou, Qiangqiang; Shi, Min; Liang, Wu; Wei, Wei; et al. (Frontiers in Neurology, 2023)
Background: Tumor Necrosis Factor (TNF) is an inflammatory cytokine that can coordinate tissue homeostasis by co-regulating the production of cytokines, cell survival or death. It widely expresses in a variety of tumor tissues and correlates with the malignant clinical features of patients. As an important inflammatory factor, the role of TNFα is involved in all steps of tumorigenesis and development, including cell transformation, survival, proliferation, invasion and metastasis. However, there is little known about the genomic profile of TNF associated with GBM. This study aimed to investigate the molecular mechanism of TNF pathway-related long noncoding RNAs (lncRNAs) and their immune characteristics in glioblastoma multiforme (GBM) patients. Methods: To identify TNF associations in GBM patients, we performed bioinformatics analysis of public database - The Cancer Genome Atlas (TCGA) and the Chinese Glioma Genome Atlas (CGGA). The ConsensusClusterPlus, CIBERSORT, Estimate, GSVA and TIDE and first-order bias correlation and so on approches were conducted to comprehensively characterize and compare differences among TNF-related subtypes. Results: Based on the comprehensive analysis of TNF-related lncRNAs expression profiles, we constructed a six TNF-related lncRNAs (C1RL-AS1, LINC00968, MIR155HG, CPB2-AS1, LINC00906 and WDR11-AS1) risk signature to determine the role of TNF-related lncRNAs in GBM. We found that this signature could divide GBM patients into different subtypes with distinct clinical and immune characteristics and prognosis. We identified three molecular subtypes (C1, C2 and C3), with C2 showing the best prognosis otherwise C3 showing the worst the prognosis. Moreover, we assessed the prognostic value, immune infiltration, immune checkpoints, chemokines cytokines and enrichment analysis of this signature in GBM. The TNF-related lncRNAs signature was tightly associated with the regulation of tumor immune therapy and could serve as an independent prognostic biomarker in GBM. Conclusion: This analysis provides a comprehensive understanding of the role of TNF-related characters, which may improve the clinical outcome of GBM patients.